Association of labour epidural analgesia with neurodevelopmental disorders in offspring: a Danish population-based cohort study. (March 2022) - Ren, Tai; Zhang, Jun; Yu, Yongfu; Pedersen, Lars H.; Wang, Hui; Li, Fei; Henriksen, Tine B.; Li, Jiong
Abstract: Background: Whether labour epidural analgesia impacts risk of neurodevelopmental disorders in offspring is unsettled, raising public and scientific concerns. We explored the association between maternal labour epidural analgesia and autism spectrum disorder, and specific developmental disorder, attention-deficit hyperactivity disorder, intellectual disability, and epilepsy in offspring. Methods: This nationwide population-based cohort study included 624 952 live-born singletons delivered by women who intended to deliver vaginally (i.e. vaginal and intrapartum Caesarean deliveries) in Denmark from 2005 to 2016. A total of 80 862 siblings discordant for exposure to labour epidural analgesia were analysed in a sibling-matched analysis. Both full-cohort and sibling-matched analyses were performed to estimate hazard ratios (HRs) of offspring risk of autism spectrum disorder, specific developmental disorder, attention-deficit hyperactivity disorder, intellectual disability, and epilepsy, according to exposure to labour epidural analgesia, adjusted for maternal socio-economic, pregnancy, and perinatal covariates. Results: In the full cohort, maternal labour epidural analgesia was associated with autism spectrum disorder in offspring (HR 1.11; 95% confidence interval [CI]: 1.04–1.18); however, in the sibling-matched analysis, no association with autism spectrum disorder was found (HR 1.03; 95% CI: 0.84–1.27). The association between labour epidural analgesia and specific developmental disorder (HR 1.12; 95% CI: 1.03–1.22) in the full cohort also disappeared in the sibling-matched analysis (HR 1.01; 95% CI: 0.78–1.31). No association between maternal labour epidural analgesia and the remaining neurodevelopmental disorders was found overall (attention-deficit hyperactivity disorder, HR 0.98; 95% CI: 0.92–1.03; intellectual disability, HR 0.98; 95% CI: 0.85–1.14; epilepsy, HR 0.89; 95% CI: 0.79–1.00) or in the sibling-matched analyses. Conclusions: Our findings did not support an association between maternal attention-deficit hyperactivity disorder and autism spectrum disorder, specific developmental disorder, attention-deficit hyperactivity disorder, intellectual disability, or epilepsy.